High-Sensitivity Whispering Gallery Mode Humidity Sensor Based on Glycerol Microdroplet Volumetric Expansion - Pauls Kristaps Reinis; Lase Milgrave; Kristians Draguns; Inga Brice; Janis Alnis; Aigars Atvars (Sensors, 2021)
We demonstrate a highly sensitive whispering gallery mode (WGM) relative humidity (RH) sensor based on a glycerol microdroplet. WGMs were excited using a 760 nm tunable semiconductor laser. We used free space coupling, which is effective when using a liquid resonator. A detailed analysis of different parameters influencing the sensor’s characteristics (sensitivity, hysteresis, resolution, stability, and temperature) is presented. The sensitivity of the sensor is one of the highest reported (2.85 nm/% RH in the range 50–70% RH with the resolution 1 × 10−4% RH). This type of humidity sensor has several advantages, such as high sensitivity, extended lifetime, good repeatability, and low cost, as well as the use of a non-toxic and environmentally friendly liquid.